DJP EMPLOYEE MANIPULATION PRACTICES FROM A CRITICAL THEORY PERSPECTIVE: THE TAX PARADOX AS AN IDEOLOGICAL TOOL AND FISCAL INSTRUMENT FOR COLLECTING STATE REVENUE - Muhammad Ikbal; Endang Herliah; Suryaningsi; Venna Puspita Sari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The integrity of tax administration in Indonesia faces significant challenges due to emerging patterns of fraud involving officials from the Directorate General of Taxes (DJP) who privately hold shares in tax consultancy firms. This phenomenon reflects a deeper systemic issue where taxation, ideally serving as both a fiscal tool and an ideological instrument for economic justice, is co-opted for personal gain. Our current study aims to critically examine how such ownership structures create conflicts of interest and facilitate corruption within the tax system. Employing a qualitative research design, we adopt a critical theory framework—particularly the Frankfurt School tradition—and apply the Fraud Triangle model to interpret fraud patterns. Data were collected through content analysis of national media coverage and in-depth interviews with taxation experts, anti-corruption officials, and academics. Findings reveal that insider access and authority are exploited to manipulate tax obligations, weakening public trust and undermining the redistributive function of tax policy. These actions create systemic risks by normalizing unethical behavior within public institutions. Our study emphasizes the need for independent oversight, stricter conflict-of-interest regulations, and reforms in ethical governance to restore institutional credibility and enhance tax compliance.